The Role of Community Leaders in Stunting Prevention in Mana Village, Muara Beliti District, Musi Rawas Regency Towards Stunting-Free Tourism Village - Sadiq, Ahmad; Hartati, Yuli; Sartono; Telisa, Imelda; Siregar, Afriyana (Research and Social Study Institute, 2022)
Stunting is one of the nutritional problems that have an impact on children's intelligence in the future. Handling stunting requires support from various parties, one of which is community leaders. This community service activity aims to invite community leaders to be actively involved in handling and preventing stunting. Community service activities begin by carrying out the Village Community Deliberation (MMD) which aims to convey existing problems and together find solutions to solve these problems. The method used in MMD activities is discussion and question and answer with community leaders. There are several activities agreed upon in the village community deliberations, namely: training and refreshment of cadres, nutrition counseling, home visits and training to make additional food from local food ingredients. The results of this community service activity show that there is an increase in the knowledge of mothers and cadres about nutrition and health as well as skills in making additional food from local food ingredients.